The Influence of Operations and Collaboration on Private Clinic Policies and Their Effects on Clinic Performance - Eric Kurniawan; Radityo Fajar Arianto (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of operations and collaboration on private clinic policies and their impact on clinic performance. Performance indicators include operational efficiency, service quality, and patient satisfaction. Using a quantitative approach, this study involved health workers and management in private clinics in Jakarta. Data analysis shows that good operations and collaboration have a significant effect on clinic policies, which are mediated by human resource management. The results of the study provide strategic insights for clinic managers to improve organizational performance.